2015
DOI: 10.1111/hae.12608
|View full text |Cite
|
Sign up to set email alerts
|

Prompt immune tolerance induction at inhibitor diagnosis regardless of titre may increase overall success in haemophilia A complicated by inhibitors: experience of two US centres

Abstract: Current guidelines recommend delaying the start of immune tolerance induction (ITI) until the inhibitor titre is <10 Bethesda units (BU) to improve success. This study was conducted to evaluate ITI outcome relative to time to start ITI from inhibitor detection irrespective of inhibitor titre. Data were retrospectively collected from two U.S. haemophilia treatment centres (HTCs) on subjects with severe/moderate factor VIII (FVIII) deficiency with inhibitors who underwent ITI. Outcomes were defined pragmatically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 39 publications
0
60
0
5
Order By: Relevance
“…28 More recently, Nakar et al reported that successful tolerance (defined in this study as a negative inhibitor titer and the ability to use fVIII for the treatment of bleeding episodes) was achieved in 13 patients with severe hemophilia A who started ITI within 1 month of inhibitor detection despite pre-ITI titers .10 BU/mL (median 25 BU/mL, range 265 BU/mL), raising doubt as to the necessity of delaying ITI. 31 In patients with high-responding inhibitors, there have been several predictors of success identified in registries and cohort studies and used in subsequent clinical trials of ITI (Table 2). [32][33][34] Race has been proposed as a risk factor, but its independent effect is unclear.…”
Section: Immune Tolerance Inductionmentioning
confidence: 99%
“…28 More recently, Nakar et al reported that successful tolerance (defined in this study as a negative inhibitor titer and the ability to use fVIII for the treatment of bleeding episodes) was achieved in 13 patients with severe hemophilia A who started ITI within 1 month of inhibitor detection despite pre-ITI titers .10 BU/mL (median 25 BU/mL, range 265 BU/mL), raising doubt as to the necessity of delaying ITI. 31 In patients with high-responding inhibitors, there have been several predictors of success identified in registries and cohort studies and used in subsequent clinical trials of ITI (Table 2). [32][33][34] Race has been proposed as a risk factor, but its independent effect is unclear.…”
Section: Immune Tolerance Inductionmentioning
confidence: 99%
“…One obvious benefit of starting ITI immediately is that it avoids the possibility of breakthrough bleeds while waiting to start ITI. A recent study suggests that the success of ITI may be improved by starting therapy immediately [9]. …”
mentioning
confidence: 99%
“…The patient showed no signs of immune deficiency and received no immune-suppressive therapy. In this case, prompt ITI after the onset of inhibitor development may have improved the chances of treatment success [18].…”
Section: Discussionmentioning
confidence: 92%